Critical evaluation of childs method for the NMR spectroscopic scaling of effective Lewis acidity: limitations and resolution of earlier discrepancies - Erdmann, Philipp; Schmitt, Manuel; Janus, Lara; Greb, Lutz (Chemistry - a European journal, 2025)
Quantifying Lewis acidity is essential for understanding and optimizing the performance of Lewis acids in diverse applications. Next to the widely accepted Gutmann-Beckett (GB) method, using triethyl phosphine oxide (TEPO) as a probe, the Childs method - employing trans-crotonaldehyde (TCA) - gained attention as an NMR-based technique for measuring effective Lewis acidity (eLA). Despite its steady use, the robustness of Childs method and its correlation with other measures remain underexplored. Previous comparisons between the GB and Childs scales revealed significant discrepancies, suggesting that hard and soft acid/base (HSAB) characteristics may be operative. In this study, we compare thermodynamic data for TCA binding to 117 Lewis acids (representing global Lewis acidity, gLA) with their corresponding NMR-induced chemical shifts in TCA. Our findings showcase notable deviations that reinforce key distinctions between eLA and gLA perspectives. Moreover, we identify significant limitations in the Childs method. First, the weak donor strength of TCA limits its applicability to only the strongest Lewis acids. Second, the exposed protons of TCA are prone to secondary interactions, obscuring the measurement of true Lewis acidity. Finally, our analysis reconciles discrepancies, refuting earlier assumptions that these arise from HSAB effects.
Zuerst veröffentlicht: 28. November 2024
Gesehen am 03.03.2025